The impact of land use change on food security under the background of rapid urbanization - a case study of Xiamen city - Zhang, Tianhai; Sun, Wenqing; Xiao, Jiangtao; Yan, Guanfeng (Environmental Research Communications, 2024)
China has undergone a long period of rapid urbanization from 2000 to 2020, resulted in huge conversion of arable land into built-up areas. This situation has raised concerns regarding food security, including issues like reduced food supply and challenges to achieving food self-sufficiency, particularly in certain regions and during special period. To address these issues, this study focuses on Xiamen, a rapidly urbanizing coastal city in China, and examined both the food supply and demand. On hand of the supply, this study mainly analyzed the attributes of the food availability, indicators like the food production (FP) of the ecosystem service value (ESV), per capita grain production, imports and exports along with food price were calculated. The findings revealed a significant expansion of built-up areas in Xiamen, mostly at the expense of arable land. The declining arable land coupled with population growth due to rapid urbanization contributed to a decrease in per capita grain production, drop to 6 kg in 2018, which is merely 1% of China’s average. A comparison of per capita grain production across various regions, as well as changes in China’s grain import and export, highlighted a notable discrepancy between urbanization rates and food security in Xiamen. It has become challenging for Xiamen to rely on outside for sustained food import. Therefore, it is imperative for Xiamen to implement a range of measures and policy interventions to ensure a certain level of food self-sufficiency and protect basic arable land.